Вплив освітнього середовища педагогічного коледжу на професійний саморозвиток майбутніх вчителів початкової школи - Смолюк, Артем; Smolyuk, A. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Стаття розкриває механізм професійного саморозвитку майбутніх вчителів початкової школи в умовах освітнього середовища педагогічного коледжу, що включає усвідомлення затруднень у своїй діяльності, аналіз його причин і умов виникнення, активне переосмислення того що відбувається і постановку перед собою нових завдань. На підставі результатів дослідження представлено нерівномірний характер цього процесу що проявляється в різких скачках показників які характеризують різні аспекти професійного становлення особистості. Провідним проявом нерівномірності виступають кризи професійного розвитку, що супроводжуються зниженням академічної успішності та навченості студентів,зростанням тривожності, незадоволеності собою і навчанням, загальним порушенням душевної рівноваги,зниженням темпів професійного саморозвитку. The goal of the research contains the clarification of features of influence of educational environment of pedagogical collage to the professional self development of future primary school teachers. The complex of methods, which are adequate to the nature of the phenomena, is used for the achieving the goal: theoretical – problematic- target analysis, systematization, generalization for comparison and confronting different approaches in the philosophy, psychology, pedagogy to different aspects of research problem, definition of categorical apparatus; empirical – diagnostical (interrogation, conversation, generalization, observation) for the clarification of levels of influence of educational environment to the рrofessional self development of future primary school teachers; methods of mathematical statistics (the data processing) for quantitative and qualitative analysis of the results of experimental work. The mechanism of the professional self development of future primary school teachers in the conditions of educational environment of pedagogical collage is opened in the article. It includes the awareness of difficulties in the activities, analysis of its appearance's causes and conditions, active rethinking of what happening and the setting new goals. On the basis of the results of investigation the uneven character of this process, which is evident in the abrupt races of indicators, which characterize different aspects the professional incipience of the personality, is presented. The main manifestation of the irregularity acts the cresses of professional development, which are accompanied with decrease of academic performance and education of the students, increasing of the anxiety, dissatisfaction with oneself and ones education, general violation of spiritual balance, decrease of temps of professional self development.
The influence of educational environment of pedagogical collage to the professional self development of future primary school teachers
Keywords: середовище; environment; освітнє середовище; початкова школа; саморозвиток; професійний саморозвиток; educational environment; primary school; self development; professional self development